Intraperitoneal chemotherapy in the management of pancreatic adenocarcinoma: A systematic review and meta-analysis. Issue 9 (September 2022) - Frassini, Simone; Calabretto, Francesca; Granieri, Stefano; Fugazzola, Paola; Viganò, Jacopo; Fazzini, Nicola; Ansaloni, Luca; Cobianchi, Lorenzo
Abstract: Background: Pancreatic cancer represents one of the leading causes of cancer-related death worldwide. Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC), normothermic intraperitoneal chemotherapy (NIPEC), and pressurized intraperitoneal aerosol chemotherapy (PIPAC) has been proven with curative intent mainly for other tumors and there is a lack of consensus regarding possible benefits also in pancreatic cancer. The present systematic review and meta-analysis aim to provide an up-to-date overview of the effectiveness and safety of intraperitoneal treatments in the management of pancreatic cancer. Methods: A systematic review of articles was conducted according to PRISMA and AMSTAR-2 guidelines. 11 studies were included in the analysis. Results: We included in our analysis 212 patients subdivided in three groups: 64 in the HIPEC group (57 with prophylactic intent and 7 with curative intent), 55 in the PIPAC group and 93 in the NIPEC group. Primary outcomes were represented by survival rates; we evidenced at an observation time of three years a survival of 24% in the HIPEC group (25.5% in the prophylactic arm and 6.2% in the curative arm), 5.3% in the PIPAC group and 7.9% in the NIPEC group. Conclusions: HIPEC could be considered as a promising technique for prophylaxis and treatment of peritoneal metastasis (PM) in case of borderline resectable and locally advanced disease. Increased survival rates emerged without additional morbidity when surgical resection and CRS are possible. In addition, our data about PIPAC and NIPEC as palliative treatment in unresectable disease seems to identify more favorable survival rates compared to literature.